(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
The transition to motherhood is a life-changing event. The aim of this paper, therefore, is to examine how mothers experience changes to their sense of self during this transition and how this can be understood from an existential perspective. Drawing on phenomenological research with first-time mothers into the transition to motherhood, it will be argued that changes to maternal identity confirm an existential view of self; that the sense of self is a process of becoming rather than a fixed entity.